Phenol Contents and Antioxidant Activity of Sonokeling (Dalbergia latifolia Roxb) Wood - Masendra Masendra; Denny Irawati; Alamratush Shoolichah Ridlo; Ganis Lukmandaru (Masyarakat Peneliti Kayu Indonesia, 2020)
Dalbergia latifolia or sonokeling is a native species of Java, Indonesia, used as an important wood for furniture and building materials, due to the high of durability and beautiful color. This study, therefore, aim to investigate the phenol composition, represented by total phenolic, flavonoid, and flavanol content, as well as antioxidant activity, conducted by DPPH (1, 1-diphenyl-2-picrylhydrazyl) method on Dalbergia latifolia wood. The sample was extracted using ethanol-toluene solvent in a Soxhlet apparatus, and subsequently subjected to column chromatography. This treatment yielded 12 fractions, which were then evaluated for phenol contents and antioxidant activity. The results showed a high antioxidant activity and total phenolic content in Fr.1- Fr.3, while latifolin was detected and characterized by GC-MS and a literature comparison. Therefore, it was established that the antioxidant activity of D. latifolia wood extractives properly correlated with the total phenolic, but not with the total flavonoid and flavanol contents.